من هدي السلف في صناعة القيادات العلمية - موسى، محمد الثاني عمر; خالد، سعيد أحمد (المؤسسة العربية للتربية والعلوم والآداب, 2023)
القيادة في النظرة الإسلامية ذات أبعاد مختلفة، فهي ذات بعد ديني وساسي واجتماعي، لذا فإن اهتمام السلف بهذا العنصر الحيوي كبير جد، ولأن الإسلام وضع عناصر مهمة في صناعة القيادة ابتداء بتقوى الله والتحلي ببعض الصفات فإن السلف الصالح قد قدموا للإنسانية نماذج حية تحتذى، والتي شكلت نقلة نوعية في القيادة حتى أصبحت مراجع مهمة اقتدى بها الخلف فيما بعد، وإن التاريخ الإسلامي خير شاهد على مثل تلك الأمثلة القيادية في الفترات المتعاقبة. وقد أثبتت هذه الدراسة أن السلف الصالح قد تركوا للمنظومات الإدارية تراكمات قيادية حية تبقى أبد الدهر أسسا إدارية فذة ترجع إليها الأمم إلى أبد الدهر مستنيرين طريقهم بهدى ربهم وسنة نبيهم صلى الله عليه وسلم واستقدام مصالح العباد هديا وتيسيرا مما هو طبيعة هذا الدين في التيسير دون التعسير وربط الحريات بالضوابط الشرعية. Leadership in the Islamic view has different dimensions, as it has a religious, political and social dimension, so the interest of the predecessors in this vital element is very great, and because Islam put important elements in the leadership industry, starting with fear of God and possessing some qualities, the righteous predecessors provided humanity with living models to be emulated, which constituted a qualitative shift in leadership until they became important references that the successor later followed, and Islamic history is the best witness to such leadership examples in successive periods. This study has proven that the righteous ancestors left the administrative systems with living leadership accumulations that will remain for eternity as unique administrative foundations to which nations will return to eternity, enlightening their path with the guidance of their Lord and the Sunnah of their Prophet, may God’s prayers and peace be upon him, and advancing the interests of the servants as guidance and facilitation, which is the nature of this religion in facilitation without difficulty and linking freedoms with legal controls.
Keywords: السلف الصالح -- التاريخ الإسلامي -- القيادات العلمية